Awareness towards Tourette Syndrome (TS) among health science and non-health science students in a private university - Tan, Kai Xuan (2022)
Background and Objectives Tourette syndrome (TS) is a neurodevelopmental disorder that causes an individual to have involuntary movements and sounds which are often called tics. This is clarified by the Diagnostic and Statistical Manual of Mental Disorder (DSM-5) with the existence of motor and vocal tics before the age of 18 which last for more than 12 months. In DSM-5, tics are defined as sudden, rapid, recurrent, nonrhythmic motor movements or vocalizations, generally preceded by urge. TS often occurs with attention-deficit hyperactivity disorder (ADHD), obsessive-compulsive disorder (OCD) and other comorbid psychological disorders or learning difficulties. This study would aim to investigate the level of awareness toward TS among health science and non-health science students at Universiti Tunku Abdul Rahman (UTAR). Methods This cross-sectional study was done among 377 students of UTAR Sungai Long and Kampar campuses. A tailor-made questionnaire was developed. The level of awareness towards Tourette Syndrome was assessed using the questionnaire. The data were analyzed using the Chi-Square test of association. Results There is no significant association between sociodemographic variables or health science and non-health science students and their level of awareness towards Tourette Syndrome. The p values are more than 0.05. Although there is no statistically significant in gender, the result showed that females have a slightly higher awareness of Tourette syndrome compared to males. Conclusion The students from health science as well as non-health science students in a private university have low awareness towards TS. In medical education, there should be more time for learning TS and tics disorder which would help the health science students to understand more about TS and the differential diagnosis.